Characteristics of Green Seaweeds from Seribu Islands and Sekotong West Nusa Tenggara Antioxidant - Chairun Nufus; Nurjanah Nurjanah; Asadatun Abdullah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Green seaweeds contain many bioactive compounds which one of them act as antioxidants as wellas rich in fibers and essential minerals. This study was aimed to determine physicochemicals propertiesof green seaweed Caulerpa lentillifera, Halimeda opuntia and Ulva lactuca. The analitycal methods of thisresearch consists of: proximate analysis, mineral composition, phytochemical compounds, heavy metalcontent and antioxidant activity of extract green seaweed by CUPRAC, DPPH and FRAP method. Theproximate analysis showed that the water content of the three seagrasses ranged from 10.83-28.41%, the ashranged from 24.97-70.66%, the fat ranged from 3.80 to 5.26%, the fiber ranged from 2, 63-3.86%, proteinranges from 0.18 to 1.43% and carbohydrates range from 10.69 to 36.49%. Seaweeds contain Ca mineralsranging from 17.95-124.39 g / kg, Na ranges from 21.16 to 34.18 g / kg. Mg ranges from 2.63-22.23 g / kg,K ranges from 2.29-12.28 g / kg and Fe ranges from 0.13-0.34 g / kg. The three seaweeds contain Pb heavymetals ranging from 13.57-37.76 mg / kg, Cu ranges from 5.02-8.32 mg / kg and Hg ranges from 0.170 to0.265.. bioactive compound extract C. lentillifera, H. opuntia and U. lactuca contains alkaloids, flavonoids,phenols hydroquinone, saponins, steroids and triterpenoids. Green seaweeds contain DPPH antioxidantactivity within IC50 values of 43,53-95,91 mg/L, CUPRAC 138.21–212.43 μmol trolox /g, FRAP 175.93–181.79 μmol trolox/g.